Recognition of liabilities arising from pension programs in accordance with IPSAS 39 - Vardiashvili, Mariam; Maisuradze, Marina (Ivane Javakhishvili Tbilisi State University Press, 2021)
The article deals with the issues related to the assessment of liabilities arising from employee benefits and recognition thereof in the financial reporting. The methods of assessing the liabilities envisaged under different pension schemes and the distinctions between them are discussed in the context of the defined contribution plan and the defined benefit plan. It is noted that under the defined contribution plan, the obligations of a public entity for each period is determined with the amount to be paid in this period, while the final costs of the defined benefit plan may be influenced by many variables.
1. Marina Maisuradze, 2014, Issues of Recording and Reporting the Pension Provision Schemes; გვ .147 https://old.tsu.ge/data/file_db/economist_faculty/konfer.pdf; 2. M. Vardiashvili, 2014, CHALLENGES OF IFRS INTRODUCTION IN GEORGIA;, https://ir.kneu.edu.ua/bitstream/handle/2010/6407/Vardiashvili.pdf?sequence=1 3. ნ.კვატაშიძე. 2014, საპენსიო უზრუნველყოფის პროგრამების აღრიცხვის საკითხები. სოხუმის სახელმწიფო უნივერსიტეტის საერთაშორისო სამეცნიერო-პრაქტიკულ კონფერენციის „თანამედროვე ეკონომიკური განვითარების აქტუალური პრობლემები“ კრებული. 4. ინსტრუქცია, „საბიუჯეტო ორგანიზაციების მიერ საჯარო სექტორის ბუღალტრული აღრიცხვის საერთაშორისო სტანდარტების (სსბასს-ების) საფუძველზე ფინანსური აღრიცხვა-ანგარიშგების წარმოების შესახებ“, 2020 , mof.ge 5. ბასს 19-დაქირავებუ მომუშავეთა გასამრჯელოები,https://www.saras.gov.ge/Content/files/ IAS-BASS/2014/2014_IAS_19_Final.pdf 6. 2. IPSAS 39, 2018 Employee Benefits ; https://www.ifac.org/system/files/publications/files/IPSAS-39-Employee-Benefits.pdf 7. PSAS 39 – EMPLOYEE BENEFITS as adopted by the Maltese Government; ttps://treasury.gov.mt/en/Documents/Government_Accounts_Directorate/IPSAS/IPSAS%20